A finite element method approach to the temperature distribution in the inner casing of a steam turbine in a combined cycle power plant. (25th July 2016) - Wang, Weiliang; Zhang, Hai; Liu, Pei; Li, Zheng; Ni, Weidou; Uechi, Hideyuki; Matsumura, Takumi
Highlights: We use FEM to study the temperature distribution of a steam turbine inner casing. The average temperature of inner casing could be obviously reduced by cooling. Circumferential non-uniform does not affect the leaking steam conspicuously. One cooling steam mass flow rate corresponds one optimal leaking cap clearance. The temperature gradient may increase in transient state. Abstract: Temperature distribution in the inner casing is a key influencing factor for the operational life of the steam turbine in a combined cycle power plant (CCPP) and it was numerically studied in this paper. The fluid side was calculated using the analytical method based on distribution of the flow resistance of each part under five cases. Heat transfer and temperature distributions on the solid side were calculated based on the results of calculation on the fluid side using the finite element method (FEM) in the steady state and the transient process at start-up stage. Results show that there is a critical leaking cap clearance which makes the mixture of cooling steam and leaking hot steam converge with the working steam at the same temperature, leading to the lowest temperature gradient at the inner casing between the mixing cavity and the working steam. The highest temperature gradient in the inner casing appears at the right ending point in the transient process, and then decreases gradually to the steady state value when the temperature of the mixing steam is lower than that of the working steam.